Genetic architecture of inducible and constitutive metabolic profile related to drought resistance in qingke (Tibetan hulless barley) - Yu, Kuohai; Wei, Lingling; Yuan, Hongjun; Zhang, Weiqin; Zeng, Xingquan; Wang, Bin; Wang, Yulin (Frontiers in Plant Science, 2022)
Qingke (Tibetan hulless barley, Hordeum vulgare L. var. nudum) is the primary food crop on the Tibet Plateau, the long-term drought and other harsh environments makes qingke an important resource for the study of abiotic resistance. Here, we evaluated the drought sensitivity of 246 qingke varieties. Genome-wide association studies (GWAS) found that root-specific expressed gene CYP84 may be involved in the regulation of drought resistance. Based on widely targeted metabolic profiling, we identified 2,769 metabolites in qingke leaves, of which 302 were significantly changed in response to drought stress, including 4-aminobutyric acid (GABA), proline, sucrose and raffinose. Unexpectedly, these drought-induced metabolites changed more violently in drought-sensitive qingkes, while the constitutive metabolites that had little response to drought stress, such as C-glycosylflavonoids and some amino acids, accumulated excessively in drought-resistant qingkes. Combined with metabolite-based genome-wide association study (mGWAS), a total of 1,006 metabolites under optimal condition and 1,031 metabolites under mild drought stress had significant associated loci. As a marker metabolite induced by drought stress, raffinose was significantly associated with two conservatively adjacent α-galactosidase genes, qRT-PCR suggests that these two genes may jointly regulate the raffinose content in qingke. Besides, as constituent metabolites with stable differences between drought-sensitive and drought-resistant qingkes, a class of C-glycosylflavonoids are simultaneously regulated by a UDP-glucosyltransferase gene. Overall, we performed GWAS for sensitivity and widely targeted metabolites during drought stress in qingke for the first time, which provides new insights into the response mechanism of plant drought stress and drought resistance breeding.